Values of Moral Education in The Film Tears at The Ujung Sajadah by Key Mangunsong and Its Relevance to Islamic Religious Education - Janingsih; Sutarman (AT-TAJDID: Journal of Islamic Education, 2025)
This research is motivated by the development of technology and information that has an impact on various aspects of life, including the decline in ethical and moral values, especially among the younger generation. This emphasizes the importance of moral education in forming individuals with character according to Islamic teachings. This study aims to (1) identify the values of moral education in the film Air Mata di Ujung Sajadah, (2) analyze its relevance to Islamic religious education, and (3) examine its benefits in strengthening students' religious values in the digital era. This study uses a qualitative method with a descriptive approach and semiotic analysis to reveal the deep meaning in the film. Data were collected through observation, literature study, and documentation. The results of the study show that this film contains moral values such as sincerity, patience, and piety, which are related to morals in the family and Islamic religious education. This film also acts as an effective media in conveying moral messages and moral education according to Islamic teachings, so that it can be a means of education for the younger generation in building better character.